Pengaruh Propaganda dan Disinformasi Tentang Opini Publik - Rambe, Anisa; Ginting, Roy Rayyan Manandha; Azzahra, Zakiya; Siregar, Fitri Holila (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses the influence of propaganda and disinformation on public opinion in the context of general elections in Indonesia. Public opinion is an important element that reflects people's views on social and political issues. Propaganda is used to shape a positive image of candidates, while disinformation spreads misleading information, which can create confusion and damage public trust. With the increasing use of social media, the spread of both phenomena has become faster and wider, contributing to social polarization. This study uses qualitative methods with descriptive analysis to identify the techniques used in propaganda and disinformation, and analyzes the role of mass media in the spread of misinformation. The results show the need for media literacy education and stricter regulations to overcome this challenge, as well as encouraging the establishment of independent fact-checking institutions.